2008
DOI: 10.1007/s11999-008-0150-6
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Shaft Fracture Resulting From Femoral Tracker Placement in Navigated TKA

Abstract: Computer-assisted navigation is a surgical tool that may decrease malalignment outliers in TKA. With any new surgical technique, there is the possibility of unexpected complications that raise caution. We report two patients with displaced femoral fractures at optical tracker pin placement sites created for routine performance of navigated TKA. Our experience suggests single bicortical 5-mm pins placed in the femoral shaft have the added risk of creating a stress riser leading to the potential for fracture. Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…CAN also comes at the expense of increased patient co-morbidities, such as tourniquet and operating time, increased instrument trays and bulky navigation equipment, and intra-operative complications. Several studies have shown fractures associated with the insertion of CAN guide pins [12][13][14] . Navigation has been shown to increase surgical operating time, with a meta-analysis demonstrated a mean increase of 23% in time [9] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CAN also comes at the expense of increased patient co-morbidities, such as tourniquet and operating time, increased instrument trays and bulky navigation equipment, and intra-operative complications. Several studies have shown fractures associated with the insertion of CAN guide pins [12][13][14] . Navigation has been shown to increase surgical operating time, with a meta-analysis demonstrated a mean increase of 23% in time [9] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, computer-navigated surgery has been shown to have increased tourniquet and operative time [9][10][11] . There have also been reports of femoral and tibial fractures from navigation pin sites [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…Two anchoring pins were inserted for the femur but three pins can be inserted for more secure fixation. Some cases with an anecdotal fractures have been reported after the placement of navigation tracker pins 9,10). There are a few reports that a smaller size and unicortical fixation pin is safer.…”
Section: Discussionmentioning
confidence: 99%
“…Some cases with an anecdotal fractures have been reported after the placement of navigation tracker pins. 9 , 10) There are a few reports that a smaller size and unicortical fixation pin is safer. In one anatomic study, the findings indicated the close proximity of the popliteal vessel to potential injury with the bicortical placement of tracker pins in the anteroposterior direction in a typical total knee approach.…”
Section: Discussionmentioning
confidence: 99%
“…Even though some authors, such as Stiehl et al (15) , have demonstrated the possibility of reducing the duration of the operation, most authors have reported that the duration of the operation increases by around 10 to 15 minutes. There have also been some reports of cases of fracture at the pin fixation sites in the tibia and femur 16 , 17 , 18 , 19 . However, these are isolated reports, and there is no evidence that the incidence of periprosthetic fractures is greater than in non-navigated arthroplasty.…”
Section: Navigation Systemsmentioning
confidence: 99%